Identification of lncRNA TRPM2-AS/miR-140-3p/PYCR1 axis's proliferates and anti-apoptotic effect on breast cancer using co-expression network analysis. Issue 6 (3rd June 2019) - Sun, Tong; Song, Yan; Yu, Hong; Luo, Xiao
ABSTRACT: Breast cancer (BC) is one of the most common malignancies occurring in women worldwide. Weighted gene co-expression network analysis (WGCNA) has not been widely utilized in uncovering the biomarkers which played pivotal roles in BC treatment. This study aimed to verify the proliferative and anti-apoptotic effect of lncRNA TRPM2-AS/miR-140-3p/PYCR1 axis on BC based on WGCNA. WGCNA was applied for determining hub genes using gene expression data gained from breast cancer and adjacent tissues which were downloaded from the Cancer Genome Atlas (TCGA) database. The correlative curves showed the correlation between OS/DFS of BC patients and TRPM2-AS expression or PYCR1 expression based on the data of survival rate of BC patients obtained from the TCGA database. QRT-PCR was employed in detecting the expression levels of TRPM2-AS, miR-140-3p and PYCR1, and western blot analysis was adopted for determination of protein expression level of PYCR1. Dual luciferase assay was applied to verify the targeting relationship between TRPM2-AS and miR-140-3p, as well as miR-140-3p and PYCR1. The roles of TRPM2-AS, miR-140-3p, and PYCR1 in proliferation, migration, and apoptosis of BC cell were identified by CCK-8 assay, cell migration assay and flow cytometry. Hub genes were also gained from WGCNA test. The prognostic study showed a significant negative correlation between the high expression of PYCR1 and TRPM2-AS and the BC survival. QRT-PCR demonstrated that PYCR1 and TRPM2-AS were both overexpressed, while miR-140-3p was greatly down-regulated in BC cell. In addition, it was validated by dual luciferase assay that miR-140-3p directly targeted both TRPM2-AS and PYCR1. Furthermore, down-regulation of TRPM2-AS and PYCR1 inhibited proliferation yet promoted apoptosis of BC cell, and up-regulation of miR-140-3p in BC cell showed the same tendency. Taken together, TRPM2-AS could promote proliferation and inhibit apoptosis of BC cell through TRPM2-AS/miR-140-3p/PYCR1 axis.